(untitled) (Journal of Kidney Cancer, 2025)
The Meet-URO score provided a more accurate prognostication than the international metastatic RCC database consortium (IMDC) risk group classification for patients with metastatic renal cell carcinoma (mRCC) by incorporating the pretreatment neutrophil-to-lymphocyte ratio (NLR) and the presence of bone metastases in different settings of the disease. To additionally validate the Meet-URO score on overall survival (OS) in a cohort of mRCC patients treated with first-line pembrolizumab plus axitinib, a post hoc analysis of the observational prospective ProPAXI study was conducted. Progression-free survival (PFS) was also considered. Harrell’s C-index was used to compare the discriminative ability on OS and PFS. Overall, the ProPAXI study included 170 patients. Both the five- and the three-risk group Meet-URO score were evaluated to account for the small sample size. The five Meet-URO risk group score showed a mOS of 27.1 months (p = 0.064) and 10.3 (p = 0.014) months for group 4 and group 5, respectively, while it was not reached for the other groups (p < 0.01). Although a worsening of PFS was observed with increasing the risk group, these differences were not statistically significant (p =0.19). Similar results were observed fot the three-risk group Meet-URO score. Both five and the three Meet-URO risk groups showed a better C-index for OS (0.69 and 0.66, respectively) compared to IMDC (0.62) and for PFS (0.60 and 0.59, respectively) compared to IMDC (0.56). These findings suggest that the Meet-URO score may provide more accurate prognostic stratification than IMDC alone in mRCC patients treated with first-line pembrolizumab and axitinib.